Crisis survival strategies: how a hotel survives during the Covid-19 pandemic - Musadad Musadad (Journal of Sustainable Tourism and Entrepreneurship, 2020)
Purpose: This study identified and explored the strategies developed by a four-star hotel in Central Java Province - Indonesia for surviving the Covid-19 pandemic. Methodology: This qualitative study collected data from an in-depth interview with the hotel’s Head of FO Department, which were analyzed inductively. Results: The hotel focused its survival strategies on four areas or aspects, including organizational targets, human resources, products and services, and marketing communication. Limitation: This study is limited in two ways, i.e. data collection method and the number of informants. Contribution: This study contributes to enriching the strategies for mitigating the disastrous impacts of the Covid-19 pandemic on the hotel business. Keywords: Covid-19, Pandemic crisis, Survival strategies